2021
DOI: 10.5604/01.3001.0014.8090
|View full text |Cite
|
Sign up to set email alerts
|

Emergency appendicectomy during COVID-19 pandemic – A single UK centre experience

Abstract: Background - In December 2019 following an outbreak of Novel coronavirus infection (COVID-19) in Wuhan, China, it spread rapidly overwhelming the healthcare systems globally. With little knowledge of COVID-19 virus, very few published reports on surgical outcomes; hospitals stopped elective surgery, whilst emergency surgery was offered only after exhausting all conservative treatment modalities. This study presents our experience of outcomes of emergency appendectomies performed during the pandemic. Methods – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Our data also does not capture attrition rates and patients lost to follow up, which may result in underreported postoperative outcomes. Although there are some studies that have shown that appendectomies were safe during the pandemic 9 , further investigation is needed to better evaluate the safety and efficacy of operative management for appendicitis during the peak of the virus. With the advent of the COVID-19 vaccines, future steps would be to investigate long term trends in the natural history of appendicitis, treatment patterns, and post-treatment course in relation to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also does not capture attrition rates and patients lost to follow up, which may result in underreported postoperative outcomes. Although there are some studies that have shown that appendectomies were safe during the pandemic 9 , further investigation is needed to better evaluate the safety and efficacy of operative management for appendicitis during the peak of the virus. With the advent of the COVID-19 vaccines, future steps would be to investigate long term trends in the natural history of appendicitis, treatment patterns, and post-treatment course in relation to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The management for acute appendicitis varied worldwide as the virus continued to spread and little was known. Given the expeditious rate of global infection spread, some countries and cities elected to proceed with nonoperative management while others elected to favor operative management when possible 8 , 9 , 10 , 11 , 12 , 13 . Given unknowns about the virus and how it affected patients with comorbidities, there was concern that operating on these patients would increase morbidity related to COVID as well as potential viral transmission from producing pneumoperitoneum.…”
Section: Introductionmentioning
confidence: 99%
“…The hospital admission rates have dropped during the quarantine. We evaluated 25 studies related with COVID-19 and AAp, and 23 of these articles reported that there was a 24% (IQR: 15%-39%; min-max: 5.4%-81%) drop in the hospital admissions due to AAp during the quarantine regulations[ 1 - 4 , 10 , 12 , 14 - 22 , 33 - 39 ]. In only 1 of the 25 studies, there was a 7% increase in the hospital admissions[ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 25 studies that were reviewed gave their results regarding negative appendectomy rates. The results of these studies showed that negative appendectomy rates dropped during the COVID-19 pandemic[ 1 , 6 , 13 - 16 , 18 , 33 , 34 , 39 ]. Five of the ten studies stated that this drop showed statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation